Pendidikan Kewirausahaan Bagi Mahasiswa Program Studi Teologi STT Star’s Lub Untuk Kemandirian Finansial Gereja - Mona Lintong; Ermin Alperiana Mosooli; Leo Mardani Ruindungan; Lefran Lefran (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
The Theological Department of Star's Lub Theological College (SLTC) has organized entrepreneurship education. One of the goals is to equip students to develop church entrepreneurship if they become pastors in the future. This study aims to determine the extent to which entrepreneurship education can provide students with the ability to build financial independence as part of church entrepreneurship. The research was conducted in two stages by combining qualitative and quantitative methods. The first stage examines the entrepreneurial abilities of 12 final-semester students who have completed entrepreneurship education, focusing on knowledge, skills, and entrepreneurial character. The method used is quantitative. The second stage uses a qualitative approach by examining the entrepreneurship education program organized by the Theological Department. The informants involved were the Chairperson of SLTC, the Deputy Head of Academic Affairs of SLTC, and lecturers in entrepreneurship courses. The results showed that the final semester students of SLTC did not yet have adequate abilities to develop the church's financial independence in the future. Entrepreneurship education is limited in curriculum, learning strategies, lecturers who support courses, and the entrepreneurial atmosphere.